2021
DOI: 10.12938/bmfh.2020-031
|View full text |Cite
|
Sign up to set email alerts
|

Methionine utilization by bifidobacteria: possible existence of a reverse transsulfuration pathway

Abstract: Although bifidobacteria are already widely used as beneficial microbes with health-promoting effects, their amino acid utilization and metabolism are not yet fully understood. Knowledge about the metabolism of sulfur-containing amino acids in bifidobacteria is especially limited. In this study, we tested the methionine utilization ability of several bifidobacterial strains when it was the sole available sulfur source. Although bifidobacteria have long been predominantly considered to be cysteine auxotrophs, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Consistent with this, bifidobacteria have long been known to be cysteine auxotrophs, although various bifidobacteria strains can also use methionine when it is the only available sulphur source. 45 A previous study with a colitis rat model also showed increased cysteine and methionine metabolism. 46 In the present study, the increased levels of cysteine and methionine metabolism, as well as glutathione metabolism in PD(−) and SPD, could result in the biosynthesis of advantageous compounds for bacteria against oxidative stress, a feature of the inflammatory environment.…”
Section: Papermentioning
confidence: 90%
“…Consistent with this, bifidobacteria have long been known to be cysteine auxotrophs, although various bifidobacteria strains can also use methionine when it is the only available sulphur source. 45 A previous study with a colitis rat model also showed increased cysteine and methionine metabolism. 46 In the present study, the increased levels of cysteine and methionine metabolism, as well as glutathione metabolism in PD(−) and SPD, could result in the biosynthesis of advantageous compounds for bacteria against oxidative stress, a feature of the inflammatory environment.…”
Section: Papermentioning
confidence: 90%
“…The AO ability of probiotic bacteria can be considered to be a result of the ability to produce amino acids in high quantities. Bifidobacteria exhibit the ability to produce amino acids with AO properties, such as cysteine and methionine [131]. Some bifidobacteria possess the genes involved in the reverse transsulfuration pathway, which produces cysteine from methionine using homocysteine as an intermediate.…”
Section: Other Probiotic Metabolites and Cellular Components With Antioxidant Propertiesmentioning
confidence: 99%
“…Some bifidobacteria possess the genes involved in the reverse transsulfuration pathway, which produces cysteine from methionine using homocysteine as an intermediate. There are genes such as ahcY that encode an S-adenosylhomocysteinase, and luxS, which encodes a S-ribosylhomocysteinase for the S-adenosyl methionine cycle [130,131].…”
Section: Other Probiotic Metabolites and Cellular Components With Antioxidant Propertiesmentioning
confidence: 99%
“…Moreover, aromatic amino acids (tryptophan and tyrosine), found mainly in BC17 CFSs at 7 h and 13 h, can be metabolized by Bifidobacterium species and converted into their lactic acid derivatives ( 29 ). Sulfur-containing amino acids are also required for the growth of bifidobacteria; indeed, some Bifidobacterium species (i.e., B. bifidum ) have been reported to be cysteine auxotrophs, while others can synthesize cysteine from methionine ( 30 ). In this regard, the presence of methionine and cysteine in BC17 CFSs (with the latter being present mainly in BC17 CFS at 7 h) can sustain the proliferation of bifidobacteria.…”
Section: Resultsmentioning
confidence: 99%